2022
DOI: 10.3390/en15166071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curing Pressure on the Long-Term Strength Retrogression of Oil Well Cement Cured under 200 °C

Abstract: The influences of curing pressure on the physical and mechanical property development of oil well cement during long-term curing were studied. Five silica-enriched cement slurries designed without and with reinforcement materials (latex fiber and nano-graphene) were autoclaved at 200 °C under two different pressures. The low pressure (50 MPa) curing was conducted for 2, 60, 90 and 180 days; the high pressure (150 MPa) curing was conducted for 2 and 360 days. The physical and mechanical properties of set cement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The mechanical property test results of the slurries have been comprehensively analyzed in our previous publications (Pang et al, 2021;Liu et al, 2022). The compressive strength test results are summarized in Table 2, where it can be seen that all slurries exhibit significant long-term strength retrogression.…”
Section: X-ray Diffraction Patterns Of Samples Cured Under High Press...mentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanical property test results of the slurries have been comprehensively analyzed in our previous publications (Pang et al, 2021;Liu et al, 2022). The compressive strength test results are summarized in Table 2, where it can be seen that all slurries exhibit significant long-term strength retrogression.…”
Section: X-ray Diffraction Patterns Of Samples Cured Under High Press...mentioning
confidence: 99%
“…Among these materials, silica flour is the most commonly used anti-strength retrogression agent and it has been proven to be quite effective for thermal recovery wells where the cement was set at a low temperature before high temperature exposure (Jiang et al, 2021;Santiago et al, 2021). However, several of our recent studies (Pang et al, 2021;Liu et al, 2022;Qin et al, 2022) have shown that silica flour is ineffective in preventing long-term strength retrogression at deep well conditions where the cement was set and cured both at 200 °C. While it is clear that the long-term strength retrogression is accompanied by cement microstructure coarsening, some inconsistent conclusions have been drawn with regard to what caused microstructure coarsening, primarily due to uncertainties in X-ray diffraction analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies tend to cast smaller cement specimens due to the accommodation limit of autoclaves on a lab scale (e.g., cylindrical specimens with a 0.5-inch diameter). Also, different sample preparation methods were adopted, such as drilling from bigger cubes (Rimmelé et al, 2008) or casting in special moulds with covers (Liu et al, 2022), see Fig. 1.…”
Section: Carbonation Of Owc: Testing Behaviour and Mitigationmentioning
confidence: 99%
“…As shown in Figure 2, NT and ANA had much higher crystallinity than NS and GNA, which means they have less structural defects and are therefore less reactive. Micro-sized alpha-Al 2 O 3 was shown to have very limited reaction with Portland cement, even at temperatures as high as 200 • C over long curing periods up to 360 days [51,52]. The high surface area and amorphous structure both contribute to the high chemical reactivity of GNA.…”
Section: Nanomaterial-enriched Slurriesmentioning
confidence: 99%